2008
DOI: 10.1016/j.juro.2008.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Size Does Not Predict Risk of Metastatic Disease or Prognosis of Small Renal Cell Carcinomas

Abstract: More than 85% of small solid renal tumors are renal cell carcinoma. The majority of localized small renal tumors can be cured with existing surgical approaches. However, there is a small but not insignificant risk of synchronous and metachronous metastatic disease and cancer associated death. Patients considering experimental therapies such as ablation and surveillance should be aware of this. Tumor size alone is not sufficient to distinguish renal cell carcinoma with benign behavior from aggressive small rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
99
3
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 20 publications
9
99
3
9
Order By: Relevance
“…19 However, a few contemporary series have reported an incidence of benign disease similar to ours. 7,20 In a study by Klatte and colleagues, which included 1208 patients with renal masses ≤4 cm, 12% had benign disease. 20 Fujii and colleagues found that 11% of renal masses were benign in patients treated with partial nephrectomy for presumed RCC.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, a few contemporary series have reported an incidence of benign disease similar to ours. 7,20 In a study by Klatte and colleagues, which included 1208 patients with renal masses ≤4 cm, 12% had benign disease. 20 Fujii and colleagues found that 11% of renal masses were benign in patients treated with partial nephrectomy for presumed RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 60% of kidney cancer cases are diagnosed incidentally, as a direct result of the more extensive use of diagnostic imaging in patients not suspected for renal cancer (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…7,20 In a study by Klatte and colleagues, which included 1208 patients with renal masses ≤4 cm, 12% had benign disease. 20 Fujii and colleagues found that 11% of renal masses were benign in patients treated with partial nephrectomy for presumed RCC. 7 They suggest that this may be due to a smaller proportion of oncocytomas in Japanese patients (2.8%) compared with the 5% reported in western countries.…”
Section: Discussionmentioning
confidence: 99%